Renewable energy and CO2 abatement in Italy. (July 2017) - Marcantonini, Claudio; Valero, Vanessa
Abstract: In order to combat global warming, Italy has committed to reduce its CO2 emissions. To this end, it has significantly encouraged renewable energy development through a variety of support schemes, ranging from green certificates to feed-in and premium tariffs. As a result, the production of electricity from renewable energy sources, in particular from solar and wind energy, has risen considerably over the past years. In this paper we review the Italian support schemes for wind and solar energy and estimate the cost of abating CO2 emissions by generating electricity from these two sources of energy for the period 2008–2011. The results show that the average costs for wind were around 165 €/tCO2 . For solar, they were much higher, around 1000 €/tCO2, as solar energy received much higher remunerations than wind energy. These costs were much higher than in Germany. This was due to the differences between the level of incentives and the different power systems. Abstract : Highlights: We estimate the cost of reducing CO2 emissions by wind and solar energy in Italy in 2008–2011. The average costs for wind were around 165 €/tCO2 . The average costs for solar were much higher, around 1000 €/tCO2 . Those costs were much higher than in Germany. This was due to the differences in the levels of incentives and to the different power systems.